SAT0381 Diagnosis and Treatment of Acute Gouty Arthritis at a University Hospital Emergency Department. (23rd January 2014) - Schlesinger, N.; Radvanski, D.; Chang Young, T.; Eisenstein, R.; Moore, D.
Abstract : Background: Acute gouty arthritis (GA) attacks account for a substantial number of emergency department (ED) visits. Objectives: Evaluate acute GA diagnosis and treatment patterns at a University Hospital ED. Methods: Retrospective chart review of consecutive ED patients 1/01/2004 - 12/31/2010 with a primary or secondary diagnosis of Gouty arthropathy and Gout NOS (diagnosis codes: 274.0 and 274.9). Outcomes: 1: Whether patient received an anti-inflammatory drug (AID) 2: level of appropriateness of treatment: most appropriate (optimal: AID in ED and prescription (Rx)) to least appropriate Results: 541 acute GA ED patient visits over 7 years. Mean age: 54.43; 79%: men. 118 (22%): first attack. 75%: attack duration ≤ 3 days. Most commonly affected: lower extremity joints. Average number of joints: 1.41 (range:1-13). 118 (22%): multiple ED visits/ same year. Consultations: 10% (n= 55) of ED visits; significantly more likely in older patients; more joints involved (p=0.003) and in patients ≥ 1 comorbidity (p=0.03). Arthrocentesis: 8% (n=42) of visits; 6% (n=7) first attack. 5.4 % (n=29) monosodium urate (MSU) crystal proven diagnosis. X-rays in 36 % (n=196). Reading: 82% (n=161): normal; 14% (n=27): OA, 1% (n=2): fracture. Drug treatment during 355 (66%) of acute GA ED visits. 154/186 (83%) not given drug in ED given Rx. Most common drugs: NSAIDs 56 % (n=198): (toradol 19% (n=69); indomethacin 19% (n=66); motrin 14% (n=49); naproxen 3% (n=11)); opiates 54% (n=190); colchicine 9% (n= 32); prednisone 9% (n=32). AID given during 44% (n= 239) of acute GA ED visits; 75% (n=408): AID Rx. 40% (n=216): AID in ED and Rx. 110 (20%) not given AID. 35% (n=190) given opiate in ED; 52% (n=282) Rx. 25% (n=137): opiate in ED and Rx. 75 (14%) of visits Glomerular filtration rate (GFR) checked. 9% (n=33) of those given NSAIDs and 6% (n=5) given colchicine GFR checked. Those who received NSAIDs or colchicine less likely to have GFR checked (p<.0001) or colchicine (p=0.02). 5% (n=25) of acute GA patient ED visits hospitalized. 76% (n=19) admitting diagnosis: acute GA. Patients given suboptimal treatment 4.58 years older than patients given optimal treatment (p=0.0008). HTN patients lower odds of receiving better treatment (p=0.0003). Patients given optimal treatment shorter attack duration (0.67 fewer days) (p=0.03). Conclusions: Arthrocentesis under-utilized, whereas, plain x-rays over-utilized during acute GA ED visits. AIDs are the mainstay of treatment in acute GA, yet, during 56% of acute GA ED visits AIDs not given. Only 40% given AID in both ED and Rx. Thus, 60% did not receive optimal treatment for acute GA. Controlled substances commonly given in ED, however, analgesia alone does not treat GA inflammation. Many GA patients have significant renal compromise, yet GFR rarely checked. Acute GA rarely led to hospitalizations. Practice patterns vary and support the need for evidence-based guidelines to help improve the diagnosis and treatment of acute GA in the ED. References: The study was supported by an investigator initiated grant from Novartis Pharmaceuticals Corporation Disclosure of Interest: N. Schlesinger Grant/research support from: Novartis, Consultant for: Novartis, Sobi, Speakers bureau: Savient, Takeda, Novartis, D. Radvanski: None Declared, T. Chang Young : None Declared, R. Eisenstein Grant/research support from: Novartis, D. Moore: None Declared